Deployment of Information Communication Technology (S) for Educational Planning in Nigeria: Problems and Way Forward - Mathew Sunday Dada; Olowonefa. J. A.; Ogunode Niyi Jacob (International Journal on Integrated Education, 2022)
Educational planning is critical to the development of education. Educational planning is handled by educational planner. The educational planner use both human and materials resources for planning of education. Information communication technology is one of the technological resources planner are using for planning of education. Educational planner in Nigeria are faced with problem deploying Information Communication Technologies (ICT) for planning of education in their respective institutions and schools. This paper discussed the concepts of ICT, educational planning and the problems of deploying information communication technologies for educational planning in Nigeria. Both primary and secondary data were used in the paper. The data were sourced from print and online resources. The paper identified inadequate funding of ICT programme, inadequate ICT facilities, corruption, high cost of ICT facilities, poor internet services and unstable power supply as problems hindering educational planner from fully deploying information communication technologies for planning education in Nigeria. Based on this problems identified, the paper recommended that government should increase the funding of ICT programme, provide adequate ICT facilities, ensure stable internet services and power supply and capacity building programme for planner. The government should subsidize the cost of ICT and fight all forms of corruption in the educational institutions and schools.